Endoplasmic Reticulum Stress Response and Transcriptional Reprogramming - Kezhong Zhang (Frontiers Research Topics, 2015)
Endoplasmic reticulum (ER) is an intracellular organelle responsible for protein folding and assembly, lipid and sterol biosynthesis, and calcium storage. A number of biochemical, physiological, or pathological stimuli can interrupt protein folding process, causing accumulation of unfolded or misfolded proteins in the ER lumen, a condition called "ER stress". To cope with accumulation of unfolded or misfolded proteins, the ER has evolved a group of signaling pathways termed "Unfolded Protein Response (UPR)" or "ER stress response" to align cellular physiology. To maintain ER homeostasis, transcriptional regulation mediated through multiple UPR branches is orchestrated to increase ER folding capacity, reduce ER workload, and promote degradation of misfolded proteins. In recent years, accumulating evidence suggests that ER stress-triggered transcriptional reprogramming exists in many pathophysiological processes and plays fundamental roles in the initiation and progression of a variety of diseases, such as metabolic disease, cardiovascular disease, neurodegenerative disease, and cancer. Understanding effects and mechanisms of ER stressassociated transcriptional reprogramming has high impact on many areas of molecular genetics and will be particularly informative to the development of pharmacologic avenues towards the prevention and treatment of modern common human diseases by targeting the UPR signaling. For these reasons, ER stress response and transcriptional reprogramming are a timely and necessary topic of discussion for Frontiers in Genetics. The important topics in this area include but not limited to: (1) ER-resident transcription factors and their involvements in ER stress response and cell physiology; (2) Physiologic roles and molecular mechanisms of ER stress-associated transcriptional regulation in lipid and glucose metabolism; (3) In vitro and in vivo models for ER stress-associated transcriptional reprogramming; (4) ER stress-associated transcriptional regulation in human disease; (5) Therapeutic potentials by targeting ER stress response pathways.